Regulating research learning spaces: An ethical-juridical perspective from South African and Canadian contexts - Rossouw, Johannes P.; Niemczyk, Ewelina K. (South African Journal of Higher Education, 2016)
This paper explores the need for formal regulations within South African and Canadian tertiary institutions’ research assistantships in which postgraduate students acquire research knowledge and skills under the supervision of project leaders. While the relationship between research assistants and project leaders is similar to those in other workplaces, educational and developmental aspects of research assistantships create a unique type of employment relationship that often is predicated on informal practices and subjective perceptions rather than on labour law or ethical standards. The absence of formal regulations such as a code of professional and ethical conduct specific to research assistantships therefore may expose research members to unnecessary challenges. Our goal in this paper is to address the dearth of literature on legal and ethical standards related to the employment of postgraduate student research assistants and to draw attention to the benefits of formal regulations within research assistantships as research learning spaces.